Identifying Criteria Preferences of Car Purchasing Among Staff in Faculty of Mechanical Engineering and Manufacturing at Universiti Tun Hussein Onn Malaysia - Bin Ngadiman, Yunos; Shiaw Wei, Chan; ShahrizatBinti Kamal, Nur (International Journal of Engineering and Technology, 2018)
An automotive industry play a vital role in economy nowadays in most of the country. It is driven to the growth of economy and development of country due to the involvement of many large company and manufacturers across the world that linked together to create diplomatic relationship across the world. The purpose of this study is to identify the level of car preferred by staff in Faculty of Mechanical Engineering and Manufacturing at Universiti Tun Hussein Onn Malaysia and to determine the whether there is a significant difference in criteria preferred for car purchasing between male and female staff. This study had used quantitative analysis and the sample size of this study are 59 out of 69 targeted respondents. The targeted respondents refer to the staff in Department of Manufacturing and Industrial Engineering in Faculty of Mechanical Engineering and Manufacturing (FKMP) at Universiti Tun Hussein Onn Malaysia (UTHM). The result shows that the criteria which are performance, safety and economy has high level of preferences among staff with 0.64 value and there is no significant difference in criteria preferred for car purchasing between male and female staff from performance aspect with significant value of 0.488, while, safety aspect significant value is 0.076 and economy aspect significant value is 0.528. This result show that there is no significant difference between male and female staff towards car purchasing and null hypothesis (Ho) is accepted.Â
Keywords: Automotive industry; criteria preference; purchasing car; quantitative analysis